Pathology of Spirocerca lupi associated oesopageal fibrosarcoma in a dog: A case report (Indian Journal of Veterinary Pathology, 2025)
Spirocerca lupi is associated with the formation of sarcomas in the oesophagus of canines. A nine-year-old male Labrador carcass was presented for postmortem examination. The necropsy revealed gelatinization of subcutaneous fat and rounded up heart with gelatinization of epicardial fat. The liver was slightly enlarged, mottled in appearance with rounded borders. Kidney showed pitted up appearance on cortex. The prostate showed moderate enlargement. A nodule measuring about 5 × 4 cm in size was observed on the distal oesophagus just proximal to gastric cardia. On incision of nodule, a reddish worm was extracted. Histopathological examination of the nodule revealed spindle to plumpy cells arranged in intertwining whorls with little amount of collagen. Degeneration and necrosis of hepatocytes were observed around the central veins whereas cells around portal triads showing mild fatty changes. Kidney revealed mononuclear cell infiltration in the interstitium along with mild fibrosis. Intestinal mucosa revealed patches of hemorrhages, mucosal necrosis and mononuclear cell infiltration in the sub mucosa. Glandular epithelium of prostate showed papillary like projections into the lumen. Based on gross and histopathological examination, the case was diagnosed as Spirocerca lupi induced oesophageal fibrosarcoma.